2011
DOI: 10.1186/1740-3391-9-4
|View full text |Cite
|
Sign up to set email alerts
|

Validation of actigraphy to assess circadian organization and sleep quality in patients with advanced lung cancer

Abstract: BackgroundMany cancer patients report poor sleep quality, despite having adequate time and opportunity for sleep. Satisfying sleep is dependent on a healthy circadian time structure and the circadian patterns among cancer patients are quite abnormal. Wrist actigraphy has been validated with concurrent polysomnography as a reliable tool to objectively measure many standard sleep parameters, as well as daily activity. Actigraphic and subjective sleep data are in agreement when determining activity-sleep patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 23 publications
1
51
0
1
Order By: Relevance
“…This study used an actigraph device (Ambulatory Monitoring Inc., New York, NY) attached to the patients' wrists for the collection of sleep-related data, which was then analyzed using Action4 software, after being downloaded in zero crossing mode. This device is an effective tool for the collection of data related to the rest-activity rhythm of cancer patients (Grutsch et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study used an actigraph device (Ambulatory Monitoring Inc., New York, NY) attached to the patients' wrists for the collection of sleep-related data, which was then analyzed using Action4 software, after being downloaded in zero crossing mode. This device is an effective tool for the collection of data related to the rest-activity rhythm of cancer patients (Grutsch et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Actigraphy employs a medical instrument to detect and record changes in activity and muscle tone (Grutsch et al, 2011). This study used an actigraph device (Ambulatory Monitoring Inc., New York, NY) attached to the patients' wrists for the collection of sleep-related data, which was then analyzed using Action4 software, after being downloaded in zero crossing mode.…”
Section: Methodsmentioning
confidence: 99%
“…Cross-sectional actigraphic studies in breast, metastatic colorectal, and non-small cell lung cancer populations have demonstrated associations between indices indicating greater dysregulation of circadian rest-activity rhythms (including lower mean activity level, less differentiated highest and lowest activity values, and delayed timing of peak activity) and greater sleep disturbance, fatigue, depressive symptoms, anxiety symptoms, and body mass index (BMI) [4-8]. Less rest-activity consistency has also been associated with flattened cortisol rhythms in breast and metastatic colorectal patients and increased inflammation and tumor-related symptoms in metastatic colorectal patients [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…18,46,47 It was suggested that treatments designed to improve circadian rhythms may also improve the sleep quality and QOL of cancer patients. 48 The American College of Sport Medicine 29 suggests that patients engage in moderate-intensity physical activity for 30 minutes each time, 5 times per week. We found that only 15.9% of patients achieved 150 min/wk of moderate-intensity physical activity as recommended by the public-health physical activity guidelines, 29 which is similar to Lin and colleagues' 28 report that 17% of Taiwanese lung cancer patients achieved the same suggested guidelines during active treatment.…”
Section: Predictors Of Objective Sleep Qualitymentioning
confidence: 99%